2016
DOI: 10.21767/2471-8173.100009
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Native Computed Tomography in Low Energy Vertebra Fracture Risk Assessment

Abstract: Background: Computed tomography (CT) can be used to accurately determine bone density in Hounsfield units (HU), the use of CT as a predictive tool has not been conclusively demonstrated in relation to low energy vertebra compression fracture (VCF).The aim of this study was to define the CT parameters that could be used to predict the risk of VCF. Materials and Methods:One hundred consecutive patients undergoing CT scans were enrolled in this study. Bone density measurements were obtained at the T10-L5 levels f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(36 reference statements)
1
2
0
Order By: Relevance
“…An a priori power calculation was performed (G*Power 3.1) based on the work of Reddy et al [27] with power at 0.80 and alpha at 0.05. Using the results for SBP as the dependent variable, the partial eta squared, determined from the F ratio and sample size was 0.43, resulting in a required sample of eight participants per group and is in agreement with the previous research [28].…”
Section: Participantssupporting
confidence: 85%
“…An a priori power calculation was performed (G*Power 3.1) based on the work of Reddy et al [27] with power at 0.80 and alpha at 0.05. Using the results for SBP as the dependent variable, the partial eta squared, determined from the F ratio and sample size was 0.43, resulting in a required sample of eight participants per group and is in agreement with the previous research [28].…”
Section: Participantssupporting
confidence: 85%
“…The scientific literature has already shown the importance of physical activity in reducing childhood obesity [25,37]. Moreover, Ubago et al [38] declared that playing football reduces body fat levels and BMI in youth development, while Mota et al [39] showed an increase in lean mass and leg strength after a six-month football program. It is important to highlight that important health problems in adults have been detected along with high BMI and percentage of body fat values during prepubertal and pubertal ages [40].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four male students from 3rd grade in one of the elementary schools that has 60 3rd grade students in the Beykoz district in Istanbul participated in the study. According to the G*Power software (V.3.1.9.7) that is used in many studies, there was statistical power of 85%, alpha of 0.05 and effect size (ES) of 0.50 [19][20][21] total of 24 male children aged under 10 years from classes A and B were randomly assigned to two groups. For age groups, the average age was taken on the day that the post-tests were conducted.…”
Section: Participantsmentioning
confidence: 99%